The addition of the thermophilic esterase EST2 influences the fatty acids and volatile compound profiles of semi hard cheeses - De Luca, Valentina (2019)
During cheese ripening the hydrolytic activities of proteases and lipases are essential to develop typical flavours; usually these activities come from lactic bacteria. A way to increase cheese flavour and/or to reduce the time of ripening is the addition of exogenous enzymes during cheese making. Actually some commercial lipases are used in cheese making, here we have evaluatedthe effect of the addition of the thermophilic esterase EST2, from Alyciclobacillus acidocaldarius, on the lipolysis and volatile compounds profiles of semi-hard cheeses. The addition of EST2 produced an increase of the degree of lipolysis up to 30% and the relative proportion of short- and medium- chain fatty acids, with respect to the control cheese. By SPME-GC-FID/MS were identified 27 and 31 volatile compounds in control and EST2-added cheeses, respectively; showing higher values than control for almost all compounds studied. EST2 addition during cheese making intensified the production of flavour compounds, suggesting a preferential release of short chain fatty acids. Considering that esterases have a different mechanism of action respect to lipases and EST2 is much more stable respect to all the commercial lipases, it could be an interesting technological tool to improve the sensory quality or to accelerate cheese ripening.